Piano Cycles “Children’s Music” No. 1 and No. 2 in the Works by Valentyn Sylvestrov: Distinctive Features of Interpretation of the Concept of Childhood - Vyshynskyi, Vitalii (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2023)
Relevance of research. Even though a lot of scholarly research has been devoted to study Sylvestrov’s music, most of it does not have a thorough analysis as it simply repeats the composer’s own remarks about his work. Therefore, there is a need to update methodology of researching Sylvestrov’s music and to find new approaches that will consider both, contemporary as well as earlier composed music. One of such insufficiently researched works is piano cycles called “Children’s Music”. Its detailed and more thorough research will allow to better understand the nature of the stylistic reversal that took place in Sylvestrov’s music in the early 1970s. Moreover, except for Sylvestrov, no other composer from the “Kyiv Avant-Garde” group composed similar children-themed cycles. This reinforces the significance of Sylvestrov’s Piano Cycles “Children’s Music” and encourages further research of the composer’s vision of the childhood notion and its features. The purpose of the article. To consider scholarly prior research of the two cycles of “Children’s Music”, and to test new approaches to identify the nuances of the composer’s vision and his interpretation of the childhood concept. Methods. The following methods were used in the research analysis: (1) analytical, that includes the analysis of existing study, views and findings, analysis of the logical idea of the “Children’s Music”); (2) semantic, that includes analysis of the cycles’ content idea and the composer’s musical interpretation of the childhood concept); (3) comparative, that includes the review and comparative analysis of the cycles. (4) To better convey the nuances or specifics of the composer’s vision of the concept of childhood and its musical expression, the researcher of this paper uses the elements of Eric Berne’s transactional analysis method and Neil Postman’s theory of childhood. The results and conclusions. It will be improper to dissect these two cycles of “Children’s Music” into “music about children” and “music for children” because it negates the opportunity to reveal the specifics of the composer’s musical interpretation of the concept of childhood. In Sylvestrov’s view, childhood is the past that cannot be changed or erased because it is an integral part of one’s personality. At the same time, childhood is not exclusively the world of children that is disconnected from adulthood. The two worlds—childhood and adulthood—overlap and merge, and create a new integral unity that is an adult child who, due to childhood experiences, rebuilds himself in the present and achieves a new level of fulfillment to move forward. This reliving and rebuilding of the past childhood experiences to renew the present and find a possible future in adulthood was expressed in Sylvestrov’s musical style at the time: the composer “reinvented” the old musical tradition and its style, and found ways to interact with the style of the present (commonly known as “avant-garde”). These two cycles of “Children’s Music” may be regarded as the beginning of Sylvestrov’s new musical sound and his original approach to music. The later works of Sylvestrov finally normalized and conceptualized the stylistic elements that the composer developed in the context of using the experience of childhood as a re-establishment restoration of integrity. Therefore, further research of the expression of childhood in Sylvestrov’s music and analysis of the child-adult interconnection disposition using Sylvestrov’s musical expression is needed.